Cost Description and Comparative Cost Efficiency of Post-Exposure Prophylaxis and Canine Mass Vaccination against Rabies in N’Djamena, Chad - Mindekem, Rolande; Lechenne, Monique Sarah; Naissengar, Kemdongarti Service; Oussiguéré, Assandi; Kebkiba, Bidjeh; Moto, Daugla Doumagoum; Alfaroukh, Idriss Oumar; Ouedraogo, Laurent Tinoanga; Salifou, Sahidou; Zinsstag, Jakob (Frontiers in Veterinary Science, 2017)
Rabies claims approximately 59’000 human lives annually and is a potential risk to 3.3 billion people in over 100 countries worldwide. Despite being fatal in almost 100% of cases, human rabies can be prevented by vaccinating dogs, the most common vector, and the timely administration of Post Exposure Prophylaxis (PEP) to exposed victims. For the control and prevention of human rabies in N’Djamena, the capital city of Chad, a free dog mass vaccination campaign was organized in 2012 and 2013. The campaigns were monitored by parallel studies on the incidence of canine rabies based on diagnostic testing of suspect animals and the incidence of human bite exposure recorded at selected health facilities. Based on the cost description of the campaign and the need for PEP registered in health centers three cost scenarios were compared: Cumulative cost efficiency of 1) PEP alone, 2) dog mass vaccination and PEP, 3) dog mass vaccination, PEP and maximal communication between human health and veterinary workers (One Health communication). Assuming ideal One Health communication, the cumulative prospective cost of dog vaccination and PEP break even with the cumulative prospective cost of PEP alone in the 10th year from the start of the calculation (2012). The cost-efficiency expressed in cost per human exposure averted is much higher with canine vaccination and One Health communication than with PEP alone. As shown in other studies, our cost effectiveness analysis highlights that canine vaccination is financially the best option for animal rabies control and rabies prevention in humans. This study also provides evidence of the beneficial effect of One Health communication. Only with close communication between the human and animal health sectors will the decrease in animal rabies incidence be translated into a decline for PEP. An efficiently applied One Health concept would largely reduce the cost of PEP in resource poor countries and should be implemented for zoonosis control in general.